Refraction and ultra‐small‐angle scattering of X‐rays in a single‐crystal diamond compound refractive lens. (13th October 2017) - Gasilov, S.; Mittone, A.; dos Santos Rolo, T.; Polyakov, S.; Zholudev, S.; Terentyev, S.; Blank, V.; Bravin, A.; Baumbach, T.
Abstract : A double‐crystal setup is used to quantify aberrations and to assess the influence of ultra‐small‐angle X‐ray scattering on the optical properties of a single‐crystal diamond compound refractive lens. Abstract : In this work a double‐crystal setup is employed to study compound refractive lenses made of single‐crystal diamond. The point spread function of the lens is calculated taking into account the lens transmission, the wavefront aberrations, and the ultra‐small‐angle broadening of the X‐ray beam. It is shown that, similarly to the wavefront aberrations, the ultra‐small‐angle scattering effects can significantly reduce the intensity gain and increase the focal spot size. The suggested approach can be particularly useful for the characterization of refractive X‐ray lenses composed of many tens of unit lenses.